The link between creativity and credibility with sustainable growth of entrepreneurial firms: evidence from Sri Lanka - Dehigama, N. D. P.; Igel, B.; Goel, G.; Fernando, A.J. (Inderscience Enterprises Ltd., 2017)
This paper shows how creativity and credibility of entrepreneurial firms in Sri Lanka contribute to sustained growth in constantly turbulent and hostile emerging market conditions characterised by high uncertainty and risk owing to political and economic instability, internal ethnic conflicts and changes in social values. This is a suitable context to test the significance of individual and corporate credibility on the survival and growth of entrepreneurial firms operating in different market environments. This study applied a mixed research methodology by combining case research and a questionnaire based large survey on the owners and top managers of 158 successful entrepreneurial firms operating in Sri Lanka. This research found that in a turbulent and hostile emerging market context, creativity and credibility significantly influence entrepreneurial firm growth. The findings offer entrepreneurs in emerging markets important insights into growth strategies for surviving and thriving in often-hostile market conditions. creativity; credibility; entrepreneurial firm growth; survival factors; emerging economy markets.